(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Religion is an ancient set of practices for attainment of self-realization. It is a part and parcel of human life. Religion has always paved way for man’s journey to harmony and integrity. In Amar Nath Prasad’s view, “Religion is an organizing idea and it is the cohesive force in man’s social structure” ( Prasad 1437). At times the differences in religious rituals and practices instigate the religious beings to turn into religious fanatics. Due to multiplicities of religious faiths, the South-Asian region is torn apart with the presence and emergence of different identity groups. The Indian subcontinent in particular has been grappling with ethnic perplexity. The events like demolition of Babri Masjid at Ayodhya in India have further aggravated this crisis.